Urban Heat Risks from Generator Use and Industrial Activity in Baghdad: Risiko Panas Urban Akibat Penggunaan Generator dan Aktivitas Industri di Baghdad - Aqeel Lami (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid urbanization and energy demands in Baghdad have intensified thermal pollution, a critical yet often neglected environmental issue. Specific Background: The pervasive use of private generators and industrial activities in Iraqi cities contributes significantly to the urban heat island (UHI) phenomenon, with implications for public health and ecosystem stability. Knowledge Gap: Despite the growing severity of heat-related risks, there is limited scientific analysis of the spatial, environmental, and health dimensions of thermal pollution in Baghdad. Aims: This study evaluated the environmental and public health impacts of urban heat pollution, quantified generator-related thermal emissions, and assessed the efficacy of sustainable cooling interventions. Results: Field and satellite data revealed surface temperature increases of up to 5.5°C in high-density areas, with generator density strongly correlated with temperature rise (r = 0.84). Respiratory disease incidence rose by 38% in affected zones (r = 0.76), while environmental degradation included reduced dissolved oxygen (–39%), elevated soil salinity (+18%), and decreased soil moisture (–42%). Novelty: This study introduces a localized, evidence-based model demonstrating the effectiveness of green technologies, such as artificial lakes and urban farming, in reducing ambient temperatures by 2.4°C. Implications: Findings underscore the urgent need for integrative urban planning incorporating sustainable cooling strategies to mitigate heat stress and protect environmental and public health. Highlights: Thermal Hotspots Identified. Private generators in dense urban areas raise surface temperatures by up to 5.5°C, significantly contributing to the urban heat island effec. Health Impacts Quantified. Respiratory disease rates increased by up to 38% in high-heat areas, showing a strong correlation (r = 0.76) between heat and health issues. Solutions Proven Effective. Implementation of artificial lakes and green farms reduced local temperatures by 2.4°C and PM₂.₅ pollution by 19%, confirming the value of sustainable cooling strategies. Keywords: Heat Pollution, Urban Heat Island, Private Generators, Respiratory Health, Sustainable Cooling